Part-time work in EU countries: labour market mobility, entry and exit - Hielke Buddelmeyer; Gilles Mourre; Melanie Ward-Warmedinger (European Central Bank (ECB), 2005)
This paper looks at the role of part-time work in labour mobility for 11 European countries. We find some evidence of part-time work being used as a stepping stone into full-time employment, but for a small proportion of individuals (less than 5%). Part-time jobs are also found to be more frequently taken up as a means to enter the labour market than to leave it. Multinomial logit regression of the determinants of part-time work reveals household composition, past labour market history and country of residence as very important for both men and women in their decision to work part time. Random effects regression controlling for individual heterogeneity, and the comparison of results for Europe and the US, reveals that a significantly higher proportion of female workers in Europe prefer inactivity and a significantly lower percentage prefer full-time, over part-time employment, than in the US, with considerable variation across EU countries.
Keywords: J21; J22; J16; J60; 330; full-time and part-time employment; gender; labour market entry and exit; Labour market mobility and flexibility; labour supply; non-employment; stepping stones; Unemployment; Teilzeitarbeit; Arbeitsmarkt; Arbeitsmobilität; Arbeitsangebot; Schätzung; EU-Staaten; Logit-Modell